Pelatihan Pengurusan Jenazah di Masjid Nurul Iman, Pasirhalang, Sukaraja, Sukabumi, Jawa Barat - Wangsadanureja, Miftah; Fatmawati, Nisa; Nabilah, Salma; Azzahra, Siti Fatimah; Mutmainah, Nurul Aini (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2024)
The management of the corpse which consists of bathing, shrouding, praying and burying the corpse in Islam is punished as fardhu kifayah. Therefore, the knowledge and skills of corpse management should be possessed by every individual Muslim who is baligh and rational. The limited number of people who know and can perform funeral arrangements in this village has encouraged members of KKN Sukabumi group two to carry out this activity. The purpose of this community service is to train the Funeral Management at Nurul Iman Mosque, Pasirhalang, Sukaraja, Sukabumi, West Java. This activity was carried out with two kinds of methods. Consisting of a direct practice or simulation method during a series of bathing and shrouding the corpse and a method of material presentation during the procession of praying and burying the corpse. It is hoped that this activity will benefit the community in terms of increasing knowledge about what is conveyed and can be used and practiced when this knowledge is needed.